Genome-wide Screening Identifies Phosphotransferase System Permease BepA to Be Involved in Enterococcus faecium Endocarditis and Biofilm Formation. (16th March 2016) - Paganelli, Fernanda L.; Huebner, Johannes; Singh, Kavindra V.; Zhang, Xinglin; van Schaik, Willem; Wobser, Dominique; Braat, Johanna C.; Murray, Barbara E.; Bonten, Marc J. M.; Willems, Rob J. L.; Leavis, Helen L.
Abstract: Enterococcus faecium is a common cause of nosocomial infections, of which infective endocarditis is associated with substantial mortality. In this study, we used a microarray-based transposon mapping (M-TraM) approach to evaluate a rat endocarditis model and identified a gene, originally annotated as " fruA " and renamed " bepA, " putatively encoding a carbohydrate phosphotransferase system (PTS) permease (biofilm and endocarditis-associated permease A [BepA]), as important in infective endocarditis. This gene is highly enriched in E. faecium clinical isolates and absent in commensal isolates that are not associated with infection. Confirmation of the phenotype was established in a competition experiment of wild-type and a markerless bepA mutant in a rat endocarditis model. In addition, deletion of bepA impaired biofilm formation in vitro in the presence of 100% human serum and metabolism of β-methyl-D-glucoside. β-glucoside metabolism has been linked to the metabolism of glycosaminoglycans that are exposed on injured heart valves, where bacteria attach and form vegetations. Therefore, we propose that the PTS permease BepA is directly implicated in E. faecium pathogenesis.